Effects of ball-milling treatment on physicochemical and foaming activities of egg ovalbumin. (November 2019) - Li, Mei; Li, Mengmeng; Tan, Wen; Liu, Xuebo; Duan, Xiang
Abstract: In egg production industry, milling and shearing is widely utilized to produce homogeneous system. This process affects functional properties of egg proteins via changing their molecular structures. In this work, ball-milling treatment is selected to explore the influence of milling process on physicochemical and foaming capacities of ovalbumin. The ball-milling treatment induced a sulfhydryl/disulfide exchange and an exposure of hydrophobic residues (surface hydrophobicity increased from 339.5 to 522.2 after 24 h of treatment). The scanning electron microscopy illustrated that an aggregation process occurred for ovalbumin. The foam structure results showed that the bubble count decreased and mean bubble size increased with increasing of milling time. Correspondingly, the foaming ability and stability of ovalbumin gradually decreased from 244.2% to 87.6%–216.8% and 76.0% after 24 h of treatment. This work offered a basic reference for application of milling treatments in food process, especially in aerated foods containing egg proteins. Graphical abstract: Image 1 Highlights: Ball-milling treatment modified secondary and tertiary structure of egg OVA. Ball-milling treatment decreased bubble count and increased bubble size of OVA. Ball-milling treatment decreased the foaming ability and stability of egg OVA.